The Effect of Partisan Representation at Different Levels of Government on Satisfaction with Democracy in the United States. Issue 4 (22nd December 2021) - VanDusky-Allen, Julie; Utych, Stephen M.
Abstract: In this paper, we analyze how variations in partisan representation across different levels of government influence Americans' satisfaction with the democracy in the United States. We conduct two survey experiments and analyze data from the 2016 American National Election Study postelection survey. We find that Americans are the most satisfied with democracy when their most preferred party controls both the federal and their respective state governments. However, we also find that even if an individual's least preferred party only controls one level of government, they are still more satisfied with democracy than if their most preferred party controls no levels of government. These findings suggest that competition in elections across both the national and state government, where winning and losing alternates between the two parties, may have positive outcomes for attitudes toward democracy.